FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINDAKAN PENCEGAHAN INFEKSI MENULAR SEKSUAL PADA PEKERJA SEKS KOMERSIAL DI LOKALISASI TELEJU PEKANBARU - Raisyifa Raisyifa; Masrizal Khaidir; Reflita Reflita (Faculty of Public Health, Andalas University, 2009)
Predicted that 1 from 3 people in the world have been got IMS. From that amount, 3 millions more are happen in South East Asia, including Indonesia. Riau is got 11th ranking in HIV-AIDS case. Data on year 2008 founded 200 case of HIV-AIDS in Pekanbaru. In localization, only afew prostitute with IMS complaint that want to check their health to medical officer. The purpose of this research is to find out which kind of Factors that Related with Prevention Acts of Sexual Transmitted Infection on a Prostitutes (PSK) in Teleja Localization, Pekanbaru City 2009. The methods of this research is used analytic with cross sectional study design. The Research population is All of prostitute in Related with Prevention Acts of Sexual Transmitted Infection on a Prostitutes (PSK) in Teleju Localization, Pekanbaru City that amount to 500 people and 60 people are sample that take with Simple Random Sampling. The results of this research founded that 60% Prostitute (PSK ) not doing prevention action as well, 43.3% PSk are low education about IMS. 46. 7% PSK still have negative attitude to IMS, 46.7% are new worker as prostitute in Teleju Localization. From bivariat analysis founded there is a significant relation between prevention action with knowledge level (p— 0,003), attitude (p=0,022) and work duration as a prostitute (p—0,036), and not founded a relation between prevention action with education level of prostitute (p=0,436). Suggested to medical officer and Self Reliance Foundation (LSM ) that are related to give a knowledge about IMS to prostitute and ask to the procures and prostitute to oblige a condom utilizing to all customers in every house to press a IMS distribution in Teleju localization. To other researcher than can take a knowledge from this research and could be completed a lack of this research.